Chapter 2 The Hohfeldian Analysis of Legal and Moral Relationships - Kramer, Matthew H. (Oxford University Press, 2024)
This chapter provides a lengthy exposition of the analysis of legal and moral positions that was propounded by Wesley Hohfeld somewhat over a century ago. It rigorously explores every aspect of Hohfeld’s analytical matrix, while also amplifying Hohfeld’s insights by showing that his matrix needs to be supplemented with several types of logical quantification. The four main entitlements delineated by Hohfeld (claim-rights, liberties, powers, and immunities) are probed sustainedly, as are the four main correlative positions (duties, no-rights, liabilities, and disabilities). The chapter likewise wards off many objections that have been leveled against the Hohfeldian analysis by critics of sundry stripes. It also recounts the several basic respects in which analyses of legal relationships differ from analyses of moral relationships.